Information aspects of multispectral active-passive radio monitoring system - Zubkov, Anatoliy; Prudyus, Ivan; Diakov, Andriy; Mymrikov, Dmytro (Видавництво Львівської політехніки, 2010)
Methodology for structural-functional construction of multispectral radio monitoring system by the criterion of information efficiency is proposed. Requirements to the main elements of the structure are determined.
Keywords: multispectral monitoring system; radiolocation image; radiometric image